SOSIALISASI MODEL PEMBELAJARAN INTERAKTIF BAGI CALON GURU SEKOLAH DASAR UNTUK MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN SISWA - Baiq, Yuni Wahyuningsih; Alimuddin, Nurkhaerat; Suranti, Ni Made Yeni; Rahmatih, Aisa Nikmah (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
The role of teachers in preparing appropriate strategies in facing the society 5.0 era is very large. One of them is preparing learning strategies as a bridge that will be used in the learning process. Learning strategies do not only include learning methods or media but the learning model used is the key to the success of the ongoing learning process. The era of society 5.0 demands technological collaboration requiring interactive learning models in the process. The interactive learning model utilizes technology in its application, namely using audio-visual elements which enable the involvement of student responses in the learning process. The stages of socialization activities for this interactive learning model for prospective elementary school teachers are: a) initial stage, b) preparation stage, c) implementation stage and d) evaluation stage. Based on the recapitulation results of the distribution of pre- and post-activity questionnaires, it shows that there is an increase in the knowledge and skills possessed by activity participants regarding interactive learning models that can be applied in the classroom. Most participants expressed interest in interactive learning models that use games in their implementation.